Análise das percepções de alunos e professores sobre o projeto de extensão de nivelamento em língua portuguesa - Gavioli, Luciana de Oliveira (2008)
This research consists in identifying and analyzing the student‟s and teacher‟s perception of satisfaction in relation to the Project of Extension of Portuguese Language Leveler, implemented in a Superior Teaching Institution in Rio de Janeiro. Distinct questionnaires were elaborated to collect data at the level of student and teacher and quantitative analyses were made using the Decision Tree Analysis. Although students and teachers point out the students‟ stored deficiencies in the basic level of learning and/or the distance from school as the principal constraints to the mastering of the mother tongue in the Superior Teaching, most of them stated that they were very much satisfied with this project. It minimizes the difficulties linked to the areas of the Portuguese Language, Reading and Textual Production and it improves the performance of the student in the academic context